The Enactment of Positive Law against Perpetrators of Sexual Deviancy in Public Space in Indonesia - Nani Widya Sari; Oksidelfa Yanto; Muhamad Iqbal; Samuel Soewita; Suhendar Suhendar (JURIS (Jurnal Ilmiah Syariah), 2023)
Problems on Lesbian, Gay, Bisexual, and Transgender (LGBT) in social life seem to be more real currently. Even though religions prohibit the behaviors of LGBT, the positive law, which is Law no.1 of 1946 on Criminal Code, does not regulate legal sanctions on LGBT. This article studies the importance of positive laws that regulate legal sanctions on the actors who practice LGBT in public. Still, as important as others, this article also tries to find out the causes of sexual disorder behaviors of LGBT. This research applies the method of normative law. Still, this research was conducted by studying the literature and collecting secondary data. After gaining the data, they were analyzed to answer the formulated problems. The research results show there must be legal sanctions on LGBT behaviors. The nation should not punish LGBT-infected people, but she must punish the people who practice LGBT in public. There are many factors causing LGBT. They are the influence of environment, childhood trauma, same-sex harassment or abuse, inferior feeling and fear of loving the opposite sex, family problem such as divorced parents, etc